Changing paradigms in inclusive education on Edgar Morin's theory: contribution to pedagogical-educational participation of inclusion students (Research, Society and Development, 2022)
With the theme Paradigm shift in inclusive education: contribution to pedagogical-educational participation of inclusion students, the objective of this article is to understand the process of paradigm shift, keeping in mind its importance for the production and acquisition of knowledge and how it can be a useful contribution to Inclusive Education in order to produce subsidies that can be incorporated into school practices and teacher training programs. The methodology used was a methodological research based on the systemic paradigm, based on the complexity theory and based on the analysis and reflection of updated texts pertinent to the descriptors of the theme. The main conclusions are that inclusive education can become a more contemporary and necessary alternative to the model that separates regular education from special education where the curricula need to adapt to projects, policies, laws and technologies in order to provide disabled students with equal learning opportunities and teachers with training through graduation, post graduation, courses, and training on inclusion. We know that all these devices are important, necessary, and urgent in the inclusive process. However, for there to be congruence between the speech and the action of including, it is necessary to raise awareness.